Studi Komparasi Pengelolaan Geopark di Dunia Untuk Pengembangan Pengelolaan Kawasan Cagar Alam Geologi Karangsambung - Setyadi, Dhika Anindhita (Magister Pembangunan Wilayah dan Kota,Undip, 2012)
The Indonesian government has set Karangsambung Geological Heritage in Central java as a geopark, a concept that the UNESCO had developed in 2004 which aims to integrate the educational, conservational and the development of the local economy. The research aims to develop an ideal model of management for the study location, based on comparative best-practices studies: data from various world-wide geoparks are collected and compared at the criteria developed by the UNESCO. The study analyses management aspects through the comparison processes, and recommends aspects which represent similarities of the characteristics and its potential for application in Karangsambung geological heritage. The research recommends a concept by the name â€œNatural Stone Parkâ€ which integrates educational, conservational and the development of local economy surrounding the study area. This concept should be accompanied by management institution structural strengthening, enforcement of regulation to protect the site, and promotional efforts to the global community.